Repatriation : factors related to individuals' expectations of international assignments - Pickard, Juana (Cranfield University, 1999)
This thesis is concerned with understanding the expectations that corporate employees form about the work- and career-related outcomes of an international assignment. Such expectations are frequently cited as being "unreasonable" and a major source of problems in the repatriation and reintegration of international returnees. There is, however, a lack of research evidence to indicate when these expectations form, how they change with time, or what factors influence their formation. The research takes a UK perspective in view of the comparatively low levels of research into British international assignees in general and their motivations and expectations in particular. The author believes this to be the first study devoted exclusively to the expectations of international assignees. The main stage of this research comprised of a postal survey to collect information about international assignees, about their work-related and career- related expectations, and about a number of factors which might prove to be precursors or predictors of expectations. Data were captured from a comparatively homogeneous population comprising British employees of profit-making companies. The main contribution of this thesis is an increase in our understanding of the work-related and career-related expectations that corporate employees form when assigned overseas. In particular, the thesis increases our knowledge of when these expectations form; how they vary with time; and what personal characteristics, actions taken by the employing organisation, and characteristics of the assignment itself affect those expectations during the course of an international assignment. A secondary contribution of this thesis is to identify a number of classes or categories of assignment that appear to be intrinsically associated with different types and degrees of expectation.